1999
DOI: 10.1037/0022-0167.46.2.233
|View full text |Cite
|
Sign up to set email alerts
|

Effects of self-efficacy-enhancing interventions on the math/science self-efficacy and career interests, goals, and actions of career undecided college students.

Abstract: This investigation evaluated the effects of both performance accomplishment and vicarious learning experiences on the math/science self-efficacy and career interests, goals (i.e., aspirations), and actions (i.e., choice of major and enrollment in courses) of career undecided college students. Undergraduates who possessed at least a moderate level of math ability and who self-reported at least a moderate level of career undecidedness were randomly assigned to 1 of 4 treatment conditions: performance accomplishm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
168
0
4

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(186 citation statements)
references
References 33 publications
8
168
0
4
Order By: Relevance
“…Studies have shown that self-efficacy is able to predict a university student's persistence in science majors as well as science career choices [9,10,13,14,16]. Additionally, researchers have found that self-efficacy can predict achievement in science for high school students [24,25] and university students [8][9][10][11][12].…”
Section: Previous Research On the Development Of Self-efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that self-efficacy is able to predict a university student's persistence in science majors as well as science career choices [9,10,13,14,16]. Additionally, researchers have found that self-efficacy can predict achievement in science for high school students [24,25] and university students [8][9][10][11][12].…”
Section: Previous Research On the Development Of Self-efficacymentioning
confidence: 99%
“…Since the 1980s an abundance of research has shown that science self-efficacy, or confidence in one's own ability to complete the actions necessary to perform a task [7], is related to success in particular fields [8][9][10][11][12], as well as a predictor of the career choice an individual will make [10,[13][14][15][16]. A few researchers in physics education have also shown a link between physics self-efficacy and success [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, students' confidence in their own ability to perform social work tasks related to research and program evaluation can be assessed by using the ESE to measure change in self-efficacy. As other studies have investigated how to best assess the effects of self-efficacy on learning and performance in various domains (Chang et al, 2014;Luzzo, Hasper, Albert, Bibby, & Martinelli, 1999;Shively, Smith, Bormann, & Gifford, 2002), this study contributes to the social work literature in this regard. The results of this study provide initial evidence that using an engaged-learning model such as service learning improves students' self-efficacy.…”
Section: Resultsmentioning
confidence: 82%
“…Similar to the effects of taking advanced math courses, students who take advanced science courses are more likely to enter STEM disciplines in post-secondary institutions (e.g., Muller, Stage, & Kinzie, 2001;Trusty, 2002;Anderson & Kim, 2006;Sahin, Morgan, & Erdogan, 2012). Like the positive relationship between math self-efficacy and STEM major choices, not surprisingly, there is a positive association between science self-efficacy and STEM major selection in college (Luzzo, Hasper, Albert, Bibby, & Martinelli, 1999;Scott & Mallinckrodt, 2005). In summary, most STEM studies have focused on traditional learning contexts in math and science disciplines, whereas relatively little attention has been paid to pre-college STEM contexts that are considered progressive learning contexts linked to practical STEM tasks.…”
Section: Pre-college Traditional Learning Factors Influencing Studentmentioning
confidence: 99%